Systematic and evolutionary engineering of a xylose isomerase-based pathway in Saccharomyces cerevisiae for efficient conversion yields - Lee, Sun-Mi; Jellison, Taylor; Alper, Hal S. (BIOMED CENTRAL LTD, 2014)
Background: Efficient xylose fermentation by yeast would improve the economical and sustainable nature of biofuels production from lignocellulosic biomass. However, the efficiency of xylose fermentation by the yeast Saccharomyces cerevisiae is suboptimal, especially in conversion yield, despite decades of research. Here, we present an improved performance of S. cerevisiae in xylose fermentation through systematic and evolutionary engineering approaches. Results: The engineering of S. cerevisiae harboring xylose isomerase-based pathway significantly improved the xylose fermentation performance without the need for intensive downstream pathway engineering. This strain contained two integrated copies of a mutant xylose isomerase, gre3 and pho13 deletion and XKS1 and S. stipitis tal1 overexpression. This strain was subjected to rapid adaptive evolution to yield the final, evolved strain (SXA-R2P-E) which could efficiently convert xylose to ethanol with a yield of 0.45 g ethanol/g xylose, the highest yield reported to date. The xylose consumption and ethanol production rates, 0.98 g xylose g cell(-1) h(-1) and 0.44 g ethanol g cell(-1) h(-1), respectively, were also among the highest reported. During this process, the positive effect of a pho13 deletion was identified for a xylose isomerase-containing strain and resulted in up to an 8.2-fold increase in aerobic growth rate on xylose. Moreover, these results demonstrated that low inoculum size and the cell transfer at exponential phase was found to be the most effective adaptation strategy during a batch culture adaptation process. Conclusions: These results suggest that the xylose isomerase pathway should be the pathway of choice for efficient xylose fermentation in S. cerevisiae as it can outperform strains with the oxidoreductase pathway in terms of yield and ethanol production and xylose consumption rates. Consequently, the strain developed in this study could significantly improve the prospect of biofuels production from lignocellulosic biomass.
Keywords: ETHANOL-PRODUCTION; PENTOSE UTILIZATION; YEAST; STRAIN; FERMENTATION; REDUCTASE; GROWTH; CATABOLISM; DELETION; PHO13